Jardins, parcs et paysages dans l’œuvre de Hermann Hesse – ou Par-delà nature et culture - Corinne Fournier Kiss (Recherches Germaniques)
The distinction between gardens and landscapes often seems obvious according to our Western conception: the first would belong to culture (gardens requiring systematic and visible human intervention), the second to nature (landscapes developing freely and independently of human action). Hermann Hesse, at numerous moments in his work when describing gardens and landscapes, also relies on this dialectic, which he develops by highlighting the contrasts between the closed and the open, the exotic and the familiar. Nevertheless, what seems at first glance to constitute an irreducible difference ends up being questioned by him, usually in the course of the same work: Gardens break down their enclosing fences; renounce their order and layout; and invade the domain of landscape. Landscapes, on the other hand, are presented as extensions of gardens and contain a biodiversity as carefully choreographed as any garden. Gardens and landscapes are “in motion” and they become not only true palimpsests overloaded with the writings of multiple places, but also function, for the observer, as a privileged means of confronting his unconscious and gaining a truer knowledge of himself.